If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying f(x) = k(x + a)(x + -1b) Multiply f * x fx = k(x + a)(x + -1b) Reorder the terms: fx = k(a + x)(x + -1b) Reorder the terms: fx = k(a + x)(-1b + x) Multiply (a + x) * (-1b + x) fx = k(a(-1b + x) + x(-1b + x)) fx = k((-1b * a + x * a) + x(-1b + x)) fx = k((-1ab + ax) + x(-1b + x)) fx = k(-1ab + ax + (-1b * x + x * x)) fx = k(-1ab + ax + (-1bx + x2)) fx = k(-1ab + ax + -1bx + x2) fx = (-1ab * k + ax * k + -1bx * k + x2 * k) fx = (-1abk + akx + -1bkx + kx2) Solving fx = -1abk + akx + -1bkx + kx2 Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Divide each side by 'x'. f = -1abkx-1 + ak + -1bk + kx Simplifying f = -1abkx-1 + ak + -1bk + kx
| 3n^2+3n-28=2n^2 | | x=30-33 | | -11x=143 | | x(x-4)=4(x+5) | | 12x+30+4x=10+x | | 16y^2/16 | | (U-4)(u-2)=0 | | x=-4x+35 | | y=-2y+300 | | 29-2x+5=y | | (8x-4)+(x^2+31)=180 | | (9+z)(4z-7)=0 | | sn=8/n | | k^3-4k^2-19k=0 | | 11.75x^3-49.35x^2+0.1=0 | | 12x^2/3x | | 100Y^2+36= | | (9+z)(-u+9)=0 | | 2^-4x^7/2^3x^-9 | | 6.9x^3=82.4x+1 | | 5(u-4)(-u+9)=0 | | 6.9x^3-82.4x-1=0 | | 13+n=24 | | 2(x+1)=55-2x | | N-4*7=n+1+4 | | 2x(x-2)=264 | | (6+w)(4w-7)=0 | | 3*lnx^2+2=14 | | 4n-1*3=9 | | (-10)+2x=10 | | 3lnx^2+2=14 | | 3/x-1/2x=1/2 |